Ductile to brittle transition depths for CVD silicon carbide and quartz. (7th March 2007) - Bhattacharya, Biswarup; Patten, John; Jacob, Jerry
Scratching experiments were performed on highly brittle materials (Chemically Vapour Deposited (CVD) Silicon Carbide (SiC) and quartz) to determine if a ductile response was possible and then to further determine the Ductile to Brittle Transition (DBT) depth, that is, critical depth of cut or penetration. Scratches were made by moving a diamond stylus and a single crystal diamond flat nose tool over a polished sample surface. RAPT Inc. had previously polished the surface to a roughness of less than 10 nm rms. During the scratching operation the horizontal forces and the Acoustic Emission (AE) signals were recorded. In post experimental analysis the depth and width of the scratch was measured using a white light interference microscope (Wyko, RST).